Learner errors related to linear equations in grade 10 - Tebeila, Stephen Malome (My University, 2016)
This research investigates three different kinds of errors made by learners using a discursive approach when dealing with equations in grade 10. The data for the study is made up of Grade 10 learners' responses to a pre-test and post-test, and is part of a much larger data set that was collected by the Wits Maths Connect Secondary Project (WMCS) in 2013. Questions like substitution and multiplying and simplifying as well as factorization are given attention as they are related to equations. The data for this study is collected by coding pre-test and post-test scripts. The data is analyzed using codes and using commognition. The role played by the equal sign in equations and operations that are performed on symbols as well as well as errors that creep in executing these operations are given attention in the study. Special attention is given to linear equations in this study. Errors identified by Brodie and Berger (2010) are confirmed. The finding is that extent to which errors made by grade 10 learners when dealing with equations stem from errors in arithmetic is substantial. The other finding is that extent to which grade 10 learners made errors related to basic algebra, when dealing with equations, is substantial.
A research project submitted in partial fulfilment of the requirements of the degree of Masters of Science (Mathematics Education) University of the Witwatersrand Johannesburg, South Africa. 10 October 2016
Keywords: Equations--Study and teaching (Secondary)--South Africa; Differential equations, Linear